Interpretation, intentionality, and sociological conditions for content identification: The study of the mind and its methodological tensions (Phenomenology, Humanities and Sciences, 2024)
This article will take the following route to explore a reflective approach to the problem of mind and its possible contents. First, we will highlight the tension between psychology and semantics in order to explain the content of mental acts from a third-person perspective. We will examine how Kant's theory of apperception explored the conditions of objective representative expression to determine the content of the intentional acts of mind. Second, we will outline how Davidson's theory of interpretation, using an extensional semantic theory based on Tarski, explores the underdeterminacy of compatible interpretive hypotheses in order to arrive at a collectively-sensitive conception of the mutual understanding and internal content of beliefs. Kant and Davidson agree that the conditions for understanding mental (or intentional) content depend on a theory of truth (or judgement) that provides the non-unilateral parameter for interpreting that content. We will then observe how this perspective accommodates skeptical notions of mind, content, and intention. We conclude with a series of remarks on the methodological tensions within psychology, showing that psychology and phenomenology face skepticism and possible absorption by sociologically infused conditions of study. The problem is that the study of the intentionality and content of mental beliefs can dissolve its object – the mind and consciousness – into a kind of ghost behind language or a mere reification of the normative conditions of rational behavior under the conditions of language influence.
Keywords: Mind; Intentionality; Interpretation; Psychology; Sociology